Pengaruh Konsentrasi Larutan Asam Sitrat terhadap Sifat Elektroda Lapisan Ganda pada Pengukuran Spektroskopi Impedansi - Adelia, Kadek Ayu Cintya; Kurniati, Ety; Kustyanto, Deny (Jurnal Fisika Unand, 2025)
Research on biological materials using dielectric materials has been widely conducted, but currently there are not many studies using electrolyte materials/solutions. The purpose of this study is to determine the relationship between solution concentration and solution impedance value, as well as the relationship between frequency and solution impedance value. This study uses the electrochemical impedance spectroscopy (EIS) technique in Citric Acid (C6H8O7) solution. The results of the study obtained indicate that the impedance value is a complex number with a real part (Z') and an imaginary part (Z''). The impedance value (Z') can be distinguished well in the frequency range of 100 Hz - 1 kHz with a concentration variation of 17.10-5 M -85.10-5 M. At low frequencies, the effect of concentration on the impedance value (Z') cannot be distinguished well, but at high frequencies, the effect of solution concentration on the impedance value can be distinguished well. In the frequency range >100 kHz, the impedance value cannot be distinguished well because the device becomes less sensitive to changes in frequency. This study shows that electrochemical impedance spectroscopy can be used to study the effects of concentration and frequency on the properties of double layers in citric acid solutions.